New insight on the interfacial interaction between multiwalled carbon nanotubes and elastomers. (12th April 2017) - Ning, Nanying; Cheng, Dongliang; Yang, Jianhua; Liu, Li; Tian, Ming; Wu, Youping; Wang, Wencai; Zhang, Liqun; Lu, Yonglai
Abstract: We studied the effect of the microstructure of multiwalled carbon nanotubes (MWCNTs) on interfacial interaction in seven kinds of MWCNT/natural rubber (NR) composites. Unexpectedly, the degree of defects (ID /IG ) of MWCNTs was found to play a key role in the interfacial interaction of MWCNT/NR composites. The content of bound rubber (BR) of the composites almost linearly increased with the increase in the ID /IG of MWCNTs. Then we studied the interfacial interaction between MWCNTs with high degree of defects and NR. Interestingly, the BR of the composites consisted of loosely adsorbed BR (LBR) and tight BR (TBR). TBR occupied about half of the total BR, and cannot be removed by extraction in hot toluene for 48 h. Meanwhile, the mobilities of macromolecules in TBR were more restricted than those in LBR. We discussed in depth the molecular origin of the interfacial interaction between defected MWCNTs and NR, and then proposed that LBR was topologically confined by the steps-like structure of defected MWCNTs whereas TBR was principally chemically bonded to MWCNTs. This study provided new insight on the interfacial interaction between MWCNTs and NR and thus provides guidance for the preparation of high-performance elastomer composites with strong interfacial interaction. Graphical abstract: